Peculiarities of destructive influence of mass media and fiction on formation of aggressive behaviour of senior pupils - Roksoliana Zozuliak-Sluchyk; Bohdan Kovbas (Vasyl Stefanyk Precarpathian National University, 2018)
The article analyzes the media as a factor in the formation of aggressive behavior and propensity to violence seniors. The features of fiction influence the aggressiveness and hostility among high school students. Keywords: aggressive behavior, media, works of fiction, high school, hostility.